Vrystaatse stryd teen eentalige naamgewing - Moll, Johan (University of the Free State, 2009)
Regarding language policy, the new South African Constitution (1996) recognised eleven official languages while clearly stipulating that measures should be put in place to raise the historically diminished usage and status of the indigenous languages. This article analyses the expectations and vigilance of white Afrikaans speakers regarding the future status and use of their language and the sensitivity and antagonism of the new rulers concerning any signs and remains of a colonialist past. The ANC’s attempt at enforcing unilingualism is analysed, as well as how concessions had to be made on both sides.

Wat taalpolitiek betref, het die nuwe Suid-Afrikaanse Grondwet (1996) in die vooruitsig gestel dat elf amptelike tale erken word, maar ook duidelik gestipuleer dat maatreëls in werking gestel moet word om die histories-benadeelde status en gebruik van die inheemse landstale te verhoog. Hierdie artikel ontleed die verwagtinge en waaksaamheid van blanke Vrystaatse Afrikaanssprekendes oor die status en gebruik van hulle taal en die gevoeligheid en antagonisme van die nuwe regeerders oor enige blyke en oorblyfsels van ’n kolonialistiese nalatenskap. Die ANC se poging om eentaligheid af te dwing word ontleed, asook hoe daar na beide kante toegewings gemaak moes word.
Keywords: Language policy; Official languages; Indigenous languages; White Afrikaans speakers; Enforcing unilingualism